2014
DOI: 10.1007/s00167-014-3431-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of meniscal allograft transplantation related to articular cartilage status: advanced chondral damage should not be a contraindication

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 34 publications
5
92
1
Order By: Relevance
“…15 Concerning isolated vs. combined MAT, a minority of authors have noted in the past that patients with accompanying deficiencies and needing multiple concomitant procedures were at greater risk of a poor postoperative outcome. 32,40,47,48 Similarly, we noted a higher postoperative Lysholm's score for isolated MAT, although there were no differences in the three other scales between the two situations. In a recent dedicated meta-analysis, Lee et al 16 found no significant differences in terms of PROMs between isolated and combined MATs.…”
Section: Discussionsupporting
confidence: 46%
“…15 Concerning isolated vs. combined MAT, a minority of authors have noted in the past that patients with accompanying deficiencies and needing multiple concomitant procedures were at greater risk of a poor postoperative outcome. 32,40,47,48 Similarly, we noted a higher postoperative Lysholm's score for isolated MAT, although there were no differences in the three other scales between the two situations. In a recent dedicated meta-analysis, Lee et al 16 found no significant differences in terms of PROMs between isolated and combined MATs.…”
Section: Discussionsupporting
confidence: 46%
“…However, this result hides the fact that there are significant differences according to the cartilage grouping. In our earlier study, 8 advanced cartilage damage appeared to be associated with failure. In this study with longer follow-up, more patients, and more events, cartilage group is shown to be a strong predictor of failure, even when balancing for potential confounders.…”
Section: Discussionmentioning
confidence: 67%
“…Failure rates varied from 0% to 33.3% with patients undergoing fresh-frozen allograft transplantation with fixation through bone tunnels in the setting of patients with International Cartilage Repair Society (ICRS) chondral grade 3b involving >1 cm 2 or worse presenting with the worst outcomes22,25). High rates of allograft survival were reported in several studies with Rue et al25) reporting an overall failure rate of MAT in only 6.5% patients, indicating a 93.5% MAT survival rate at a mean follow-up of 37.2 months and McCormick et al16) reporting a 95% allograft survival rate at a mean of 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several studies reporting low failure rates, several revealed high rates of complications (as high as 30%–46%) including tears requiring repair, allograft removal, as well as infections requiring antibiotic treatment and lavage16,18,19,21,22).…”
Section: Resultsmentioning
confidence: 99%